Using Midlevel Providers in Interventional Radiology - Beach, Debra (Thieme Medical Publishers, 2006)
Developing and implementing clinical services, including consultations, rounds, and clinic, is time-consuming, and for the interventional radiologist this means time away from the interventional laboratory. Using a team approach to providing clinical services is logical, and the midlevel provider is a perfect fit for an interventional radiology team. Midlevel providers can be grouped into two categories, advanced practice nurses (APNs) and physician's assistants (PAs). Under the umbrella of APN are several specialties including the nurse practitioner (NP), clinical nurse specialist (CNS), certified nurse midwife, and certified nurse anesthetist. The midlevel providers that are particularly suited for interventional radiology are the NPs, CNSs, and PAs. This article discusses midlevel providers in-depth including skills, limitations, and expenses.